2020
DOI: 10.21203/rs.3.rs-120562/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Locus-specific induction of gene expression from heterochromatin loci during cellular senescence

Abstract: Cellular senescence is a fate-determined state, accompanied by reorganization of heterochromatin. While lineage-appropriate genes can be temporarily repressed through facultative heterochromatin, stable silencing of lineage-inappropriate genes often involves the constitutive heterochromatic mark, histone H3K9me3. The fate of these heterochromatic genes during the chromatin reorganization accompanying senescence is unclear. Here we show a small number of lineage-inappropriate genes are derepressed in senescent … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 75 publications
(120 reference statements)
0
7
0
Order By: Relevance
“…NLRP3 inflammasome activation has been linked to amplified inflammatory cytokine signaling in senescent cells (259,260). The expression of NLRP3 inflammasome related molecules (NLRP3, ASC, caspase-1, IL-1β, IL-18) is increased in the synovial tissue of collagen-induced arthritis (CIA) mice (88,192,261) and MIA-induced OA rats (89,90).…”
Section: Mitochondrial Mediated Nlrp3 Inflammasome Activationmentioning
confidence: 99%
“…NLRP3 inflammasome activation has been linked to amplified inflammatory cytokine signaling in senescent cells (259,260). The expression of NLRP3 inflammasome related molecules (NLRP3, ASC, caspase-1, IL-1β, IL-18) is increased in the synovial tissue of collagen-induced arthritis (CIA) mice (88,192,261) and MIA-induced OA rats (89,90).…”
Section: Mitochondrial Mediated Nlrp3 Inflammasome Activationmentioning
confidence: 99%
“…Thus, these genes are regulated during epidermal differentiation in a spatiotemporal manner through a timely reduction of facultative heterochromatin activity (marked by histone H3K27me3) [55]. These genes have such a specialised function that they are tightly silenced in other cell types, such as fibroblasts, where the EDC is enriched for histone H3K9me3 (a marker of constitutive heterochromatin) and heavily compacted at the nuclear periphery, exemplifying a stable silencing mechanism of ‘lineage‐inappropriate genes’ [56]. However, our recent study revealed that, in fibroblasts, genes within this locus, most notably Late cornified envelope 2 ( LCE2 ) genes, are ectopically de‐silenced during senescence but not upon acute DNA damage treatment nor E1A/RAS‐transformation, in a p53‐dependent manner [56].…”
Section: Coordinating P53 Activity During Senescencementioning
confidence: 99%
“…These genes have such a specialised function that they are tightly silenced in other cell types, such as fibroblasts, where the EDC is enriched for histone H3K9me3 (a marker of constitutive heterochromatin) and heavily compacted at the nuclear periphery, exemplifying a stable silencing mechanism of ‘lineage‐inappropriate genes’ [56]. However, our recent study revealed that, in fibroblasts, genes within this locus, most notably Late cornified envelope 2 ( LCE2 ) genes, are ectopically de‐silenced during senescence but not upon acute DNA damage treatment nor E1A/RAS‐transformation, in a p53‐dependent manner [56]. Surprisingly, the LCE2 genes are induced without apparent loss of the H3K9me3 mark, but rather through physical decompaction of the locus.…”
Section: Coordinating P53 Activity During Senescencementioning
confidence: 99%
See 2 more Smart Citations